Effect of smart textile metamaterials on electromagnetic performance for wireless body area network systems. Issue 14 (July 2019) - Moradi, Bahareh; Fernández-García, Raul; Gil, Ignacio
In this work, the utilization of different textile materials for manufacturing of metamaterial with the aim of controlling the signal propagation in smart textile applications is investigated. The performance of composite structures of embroidered yarn conductor transmission lines loaded with split-ring resonator geometries in felt and cotton substrates are reported. The proposed structure allows propagating or filtering the transmitted signal in the microwave frequency range. The experimental results exhibit a rejection band between 1.3 and 2.6 GHz for felt substrate and between 1.6 and 2.6 GHz for cotton substrate with stop-band levels lower than –20 dB. The presented e-textile structures are designed, electromagnetically simulated and measured. The measured results are in good agreement with three-dimensional electromagnetic simulations. The effect of bending of the e-textiles for realistic scenarios is also studied. The experimental results show that by changing the radius of bending from 10 to 65 mm, the resonance frequency is shifted up 290 and 144 MHz for cotton and felt substrates, respectively.